A tensegrity driven DNA nanopore. Issue 27 (5th July 2017) - Mendoza, O.; Calmet, P.; Alves, I.; Lecomte, S.; Raoux, M.; Cullin, C.; Elezgaray, J.
Abstract : Design and characterisation of a DNA nanopore which modifies its conductivity upon hybridization with a specific DNA signal. Abstract : Control of transport across membranes, whether natural or synthetic, is fundamental in many biotechnology applications, including sensing and drug release. Mutations of naturally existing protein channels, such as hemolysin, have been explored in the past. More recently, DNA channels with conductivities in the nanosiemens range have been designed. Regulating transport across DNA channels in response to external stimuli remains an important challenge. Previous designs relied on steric hindrance to control the inner diameter of the channel, which resulted in unstable electric signatures. In this paper we introduce a new design to control electric channel conductance of a DNA nanopore. The tensegrity driven mechanism inhibits the flux of small analytes while keeping a tightly controlled ionic transport modulated by the addition of specific DNA sequences. Current signals are clearly defined, with no sign of gating, opening new perspectives in single molecule DNA sensing.